Chapter Postcolonial Italian Studies: Rhizomatic Notes from the South - Zuccala, Brian (Biblioteca di Studi di Filologia Moderna, 2022)
This essay draws on the first (of two) edited volumes of ISSA dedicated to "Postcolonialismi Italiani ieri e oggi appunti (sudafricani) per una (ri)concettualizzazione 'rizomatica' dei postcolonial Italian studies" (Virga, Zuccala 2018) and on some of the new concepts introduced therein. The essay tackles in a more thorough fashion and from a broader perspective some of the methodological and terminological issues raised - albeit in a necessarily cursory manner (and in Italian) - in Virga and Zuccala 2018. The essay starts by geographically positioning writers in the context of global academia and claiming an epistemological consequence of their geographical position. It then gives an overview of the field of postcolonial Italian studies in order to explain how the concept of rhizome, when applied meta-critically to the whole field, might provide a useful starting point for a paradigmatic reconceptualization of postcolonial Italian studies.